Portfolio of Photographs - Lévesque, Andrée; Lévesque, Andrée (Madeleine Parent: Activist, 2005)
Annotated reproductions of photographs of Parent as well as pertinent news clippings.
Keywords: Biography; Feminism; History; Parent, Madeleine, 1918-2012; Social conditions; Syndicalism; Women political activists